Use of maker culture in the educational context: Systematic literature review (Research, Society and Development, 2022)
The creative process is extremely important for the development of a society, therefore, one of the functions of school institutions is to provide assistance to students in the development of their skills to think, in an inventive way, in order to solve problems that arise in everyday life. ., with direct experience in problem solving, added to intuition, trial and error, in the elaboration of objects, gave rise to the maker movement, which aims to stimulate collaborative intelligence, the process of creativity and the practical issue in the use of technological resources, motivated by fun and self-fulfillment. The main objective of this research is to demonstrate a broad view of studies on maker culture in the educational context. To support the research, there was a need for a systematic literature review, through the analysis of theories referring to the maker movement and its importance in education. It was found through the research that the topic has been attracting greater attention from the scientific community, both internationally and nationally, and it can be seen that most studies are directed to the domain of Science and Technology learning. However, there is still a clear need for more research regarding the application of the maker movement in the educational sphere, thus providing for an exploration and further development of new tools, in addition to highlighting in the research the lack of new instruments to measure its real effectiveness in the educational process.